Cucurbitacin B Exerts Antiaging Effects in Yeast by Regulating Autophagy and Oxidative Stress. (2nd June 2019) - Lin, Yanfei; Kotakeyama, Yuki; Li, Jing; Pan, Yanjun; Matsuura, Akira; Ohya, Yoshikazu; Yoshida, Minoru; Xiang, Lan; Qi, Jianhua
Abstract : The budding yeast Saccharomyces cerevisiae has been used as a model organism for the basic mechanism of aging, which provides useful assay systems for measuring both replicative and chronological lifespans. In the course of our screening program for substances that extend replicative lifespan, cucurbitacin B (CuB) was found as a hit compound from a compound library, which contains cerebrosides, phenols, sesquiterpenoid, triterpenoids, and sterols isolated from natural products by our research group. Importantly, it prolonged not only the replicative lifespan but also the chronological lifespan in yeast. CuB increased ATG32 gene expression, suggesting that CuB induces autophagy. Indeed, the GFP signal generated from the cleavage of GFP-Atg8, which is a signature of autophagy, was increased upon CuB treatment. On the other hand, CuB failed to increase the chronological lifespans when either ATG2 or ATG32, essential autophagy genes, was deleted, indicating that the lifespan extension by CuB depends on autophagy induction. Furthermore, CuB significantly increased superoxide dismutase (Sod) activity and the survival rate of yeast under oxidative stress, while it decreased the amount of reactive oxygen species (ROS) and malondialdehyde (MDA) production, indicating that CuB has activity to antagonize oxidative stress. Additionally, CuB did not affect replicative lifespans of sod1, sod2, uth1, and skn7 mutants with the K6001 background, indicating that aging-related genes including SOD1, SOD2, UTH1, and SKN7 participate in the antiaging effect of CuB. These results suggest that CuB exerts antiaging activity by regulating autophagy, ROS, antioxidative ability, and aging-related genes. Finally, we discuss the possible intracellular targets of CuB based on the phenotypic comparison between the CuB and global gene deletion databases.